Clinico-demographic, Thyroid, and Lipid Biomarkers in Patients with and without Type 2 Diabetes Mellitus in a Paramilitary Hospital, Nepal - Shrestha, Mahendra Raj; Shrestha, Apurba; Bhat, Dinesh Singh; Maharjan, Rajendra (Medical Journal of Armed Police Force Nepal, 2025)
Introduction: Diabetes disrupts the hypothalamic regulation of thyroid-releasing hormone and impacts the synthesis of triiodothyronine and thyroxine, leading to disrupted lipid biomarker levels. This study aimed how HbA1c correlates with body mass index, thyroid and lipid biomarkers in patients with and without type 2 diabetes mellitus.Methods: This case-control study was conducted at the Paramilitary Hospital between July 2023 and June 2024, along with 202 type 2 diabetes mellitus patients (case) and 211 control. Ethical approval was taken from Ethical Review Board (Reference number: 3795). 202 Cases with Clinico-demographic and anthropometric variables were collected. Fasting venous blood samples were analyzed for HbA1c, thyroid, and lipid profiles. Data were analyzed using Statistical Package for the Social Sciences version 17.Results: Among 2,488 hospital visitors, the prevalence of type 2 diabetes mellitus was 202 (8.12%) cases. The odds of having elevated HbA1c were significantly higher among patients with diabetes (OR = 64.7; 95% CI: 34.01–122.67). Additionally, increased body mass index showed (OR = 1.16; 95% CI: 0.78–1.72), while hypertriglyceridemia (OR = 6.4; 95% CI: 4.12–9.94) and elevated TSH levels (OR = 48.45; 95% CI: 11.64–200.25) were strongly associated with type 2 diabetes mellitus.Conclusions: This study found that Type 2 Diabetes Mellitus prevalence was low in the paramilitary hospital. These patients had higher levels of HbA1c, body mass index, triglycerides, and thyroid stimulating hormone. Early identification and management of these parameters could improve clinical outcomes and reduce disease burden.